Guide to Diagnosis and Appraisal of AAR Damage to Concrete in Structures Part 1 Diagnosis (AAR 6.1) - Godart, Bruno; de Rooij, Mario; Wood, Jonathan G.M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book describes procedures and methodologies used predominantly to obtain a diagnosis of damaged concrete possibly caused by Alkali-Aggregate Reaction (AAR). It has two primary objectives, namely firstly to identify the presence of AAR reaction, and whether or not the reaction is the primary or contributory cause of damage in the concrete; and secondly, to establish its intensity (severity) in various members of a structure. It includes aspects such as field inspection of the structure, sampling, petrographic examination of core samples, and supplementary tests and analyses on cores, such as mechanical tests and chemical analysis. Evaluation of test data for prognosis, consequences and appraisal will be more fully set out in AAR-6.2.
1. Introduction: 1.1 Why the need for a diagnosis document -- 1.2 Scope -- 1.3 Definitions -- 2 Alkali-Aggregate Reaction: 2.1 Introduction -- 2.2 Alkali -- 2.3 Aggregates -- 2.4 Water -- 2.5 Pessimum behaviour -- 2.6 Summary -- 3 Symptoms of an expansive reaction during routine inspection: 3.1 General inspection remarks -- 3.2 Review of existing records -- 3.3 Planning of a comprehensive on-site inspection -- 3.4 The routine on-site inspection -- 3.5 Concrete surface features suggestive of AAR -- 3.6 First assessment of field observations -- 4 Confirmation investigation: 4.1 Introduction -- 4.2 Available methods, personnel and expertise -- 4.3 Approach for diagnosis of AAR in structures -- 4.4 On-site sampling for AAR confirmation -- 4.5 Visual examination of cores -- 4.6 Petrographic examination -- 4.7 Additional tests -- 5 Severity investigation: 5.1 Introduction -- 5.2 Field investigation -- 5.3 Laboratory tests -- 5.4 Summary of diagnosis -- 6 Reporting: 6.1 Purpose -- 6.2 Scope -- 6.3 Objectives of the investigation -- 6.4 Information concerning the structures -- 6.5 Methods and techniques used -- 6.6 Interpretation of results -- 6.7 Conclusions -- 6.8 Author -- References -- Appendix 1. Proceedings of ICAAR -- Appendix 2. Diagnosis of AAR within an overall investigation.
Keywords: Engineering; Mechanical engineering; Building construction; Materials; Engineering; Building Repair and Maintenance; Structural Materials; Structural Mechanics